Millimeter-wave reconfigurable antenna based on VO2 ink achieved by a simple process - Suwu Ma; Wanchen Yang; Jinghao Li; Quan Xue; Wenquan Che (Materials & Design)
The growth of communication demands have boosted the development of millimeter-wave technology, as the spectrum migrates to higher frequencies. And reconfigurable antennas emerge as a promising solution for complex communication systems. Nevertheless, the deployment of millimeter-wave reconfigurable antennas is impeded by the limitations of conventional switching devices like PIN diodes and varactors, which are unsuitable for millimeter-wave applications. Vanadium dioxide (VO2), as a phase-change material, possesses high isolation and low loss at millimeter-wave band, enabling it to function effectively as a switching device. Despite its advantages, traditional VO2 film fabrication methods are costly and time-consuming, greatly limiting its application. This paper presents a simple VO2 ink fabrication technique, which is cost-effective, stable, and easy to integrate. Based on the VO2 ink, a frequency-reconfigurable millimeter-wave antenna is designed and fabricated. The results confirm the feasibility of using VO2 ink for millimeter-wave applications and demonstrate its tolerance to fabrication inaccuracies, marking a significant advancement in the design of reconfigurable antennas and broadening the potential for future research and applications.